Overview and comparison of the clinical scores in hidradenitis suppurativa: A real-life clinical data - Daoud, Mathieu; Suppa, Mariano; Benhadou, Farida; Daxhelet, Mathilde; Njimi, Hassane; White, Jonathan; Jemec, Gregor; del Marmol, Véronique (Frontiers in Medicine, 2023)
Introduction Partly due to its clinical heterogeneity, hidradenitis suppurativa (HS) is difficult to score accurately. This is illustrated by the large number of disease scores. In 2016, a systematic review by Ingram et al. reported the use of about thirty scores, and since then, this number has increased further. Our aim is twofold: to provide a succinct but detailed narrative review of the scores used to date, and to compare these scores with each other for individual patients. Materials and methods The review of the literature was done among articles in English and French, on Google, Google scholar, Pubmed, ScienceDirect and Cochrane. To illustrate the differences between scores, data from some Belgian patients included in the European Registry for HS were selected. A first series of patients compares the severity of the following scores: Hurley, Hurley Staging refined, three versions of Sartorius score (2003, 2007, 2009), Hidradenitis Suppurativa Physician Global Assessment (HS-PGA), International Hidradenitis Suppurativa Severity Scoring System (IHS4), Severity Assessment of Hidradenitis Suppurativa (SAHS), Hidradenitis Suppurativa Severity Index (HSSI), Acne Inversa Severity Index (AISI), the Static Metascore, and one score that is not specific to HS: Dermatology Life Quality Index (DLQI). A second set of patients illustrates how some scores change over time and with treatment: Hurley, Hurley Staging refined, Sartorius 2003, Sartorius 2007, HS-PGA, IHS4, SAHS, AISI, Hidradenitis Suppurativa Clinical Response (HiSCR), the very new iHS4-55, the Dynamic Metascore, and DLQI. Results Nineteen scores are detailed in this overview. We illustrate that for some patients, the scores do not predictably and consistently correlate with each other, either in an evaluation of the severity at a time-point t, or in the evaluation of the response to a treatment. Some patients in this cohort may be considered responders according to some scores, but non-responders according to others. The clinical heterogeneity of the disease, represented by its many phenotypes, seems partly to explain this difference. Conclusion These examples illustrate how the choice of a score can lead to different interpretations of the response to a treatment, or even potentially change the results of a randomized clinical trial.